Perbandingan Metodologi Fatwa antara Ulama Klasik dan Modern: Ushul Fikih dan Kontekstualisasi Ijtihad - Aji, Ahmad Mukri (BULETIN ADALAH, 2025)
This study compares the methodologies of fatwa formulation between classical and modern scholars through a comparative ushul al-fiqh perspective, emphasizing the contextualization of ijtihad. It argues that classical fatwas were predominantly text-based, madhhab-oriented, and individual in nature, reflecting relatively stable social contexts. In contrast, modern fatwa methodologies respond to complex contemporary realities through collective ijtihad, interdisciplinary analysis, and a strong orientation toward maqāṣid al-sharī‘ah. Despite methodological shifts, both approaches remain grounded in ushul al-fiqh. The study concludes that modern fatwa methodology represents a contextual extension of the classical tradition, balancing textual fidelity with social relevance to ensure Islamic law remains adaptive, legitimate, and responsive to modern challenges. Keywords: Fatwa Methodology, Ijtihad, Ushul al-Fiqh